The Impact Of ESG (Environmental, Social, And Governance) Regulations On Corporate Legal Liability - Untari, Dhian Tyas; Zulfikar , Pandri; Maulana, Firman; Syarif, Ahmad; Ardini, Nyayu Maya; Agus, Andi Adri; Putri, Cory Kartika; Nurhadi, Ahmad; Maulana, Wachid; Sudhana, Hari; Susi , Agustine; Mustofa, Muhammad Ali; Ferdiansyah, Dony; Mahfudlon; Ilman, La; M. Umar Kelibia; Zainal, Toyib; Aji, Ibrahim; Afifah, Yasfika Ely Nur; Setiyawan, Agus Eko (CITACONOMIA : Economic and Business Studies, 2026)
This study examines the influence of Environmental, Social, and Governance (ESG) regulations on corporate legal liability within the evolving framework of modern business law. As global business practices shift toward sustainability and accountability, ESG has transformed from a voluntary guideline into a mandatory regulatory standard that shapes corporate behavior. This research employs a qualitative and normative approach by analyzing relevant legal frameworks, scholarly literature, and case studies to explore how ESG regulations affect corporate responsibility. The findings indicate that ESG regulations significantly expand the scope of corporate legal liability beyond traditional financial obligations to include environmental protection, social responsibility, and governance transparency. Companies are increasingly held accountable through civil, criminal, and administrative sanctions for non-compliance with ESG-related standards. The study also highlights that effective ESG implementation can serve as a preventive mechanism, reducing legal risks and enhancing corporate governance. However, challenges remain, particularly in terms of regulatory harmonization, enforcement mechanisms, and varying levels of compliance across jurisdictions. This research concludes that ESG regulations play a critical role in strengthening corporate accountability and promoting sustainable business practices. Integrating ESG into corporate legal frameworks is essential for balancing economic objectives with social and environmental responsibilities in the long term.